Dose-Response Moringa Oleifera Extracts on Lactation Outcomes In Breastfeeding Women - Irmawati Irmawati; Mohammad Zen Rahfiludin (Jurnal Kesehatan Masyarakat, 2026)
Introduction: Herbal galactagogues such as Moringa oleifera are traditionally used to enhance breast milk production. However, evidence regarding optimal dosage is limited. This study aimed to evaluate the effects of three different doses of Moringa oleifera extract (250 mg, 650 mg, and 800 mg) on breast milk production in breastfeeding mothers. Methods: a quasi-experimental pretest posttest was conducted among 89 postpartum women from three Primary Health Centre areas in Semarang, Central Java, Indonesia. Participants received 250 mg (n=28), 650 mg (n=30), or 800 mg (n=31) of Moringa oleifera extract once daily for 14 days. Outcomes were infant weight gain, bowel movement frequency, and urination frequency. Data were collected from October 2024 to March 2025 and analysed using paired t tests and Kruskal-Wallis tests (p<0.05). Results: All dosage groups showed improvements in indicators of breast milk production. No statistically significant differences were observed between groups (p>0,05). The 650 mg group recorded the highest mean infant weight gain, whereas the 250 mg group showed the greatest increases in bowel movements and urination frequency. Conclusions: Moringa oleifera extract at 250, 650, and 800 mg/day over 14 days supported breast-milk production. Further studies are needed to clarify the dose response relationship.